Forgiveness of Parent in The Silariang Incident - Nurdin, Muh Nur Hidayat; Zainuddin, Kurniati; Piara, Muhrajan; Fadilah, Nurul (Jurnal Psikologi TALENTA, 2025)
Silariang is one form of cultural marriage of the Bugis-Makassar community that is not expected to occur because it causes many negative impacts both on the perpetrators of silariang and their families. so that it is usually difficult to accept and forgive the perpetrators of silariang. This study aims to find out more about the dynamics of forgiveness from parents whose children do silariang. This study uses a qualitative research method with a case study method using semi-structured interviews as a data collection technique. Data validity techniques are carried out by triangulation and member checking. The results of the study indicate that the process of forgiving parents in the silariang incident requires a different time span and different stages of the process for each respondent, where respondents, where respondents who are mothers forgive their children more quickly than respondents who are fathers. Respondents go through all aspects and stages of forgiveness. Forgiving makes respondents free from negative feelings and thoughts that have the potential to have on going negative psychological and physical impact.